2020
DOI: 10.1002/jssc.202000490
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lipophilic components in Citri Reticulatae Pericarpium cultivars by supercritical CO2 fluid extraction with ultra‐high‐performance liquid chromatography–Q Exactive Orbitrap tandem mass spectrometry

Abstract: To systematically identify the lipophilic constituents of Citri Reticulatae Pericarpium from different cultivars, supercritical CO2 fluid extraction and ultra‐high‐performance liquid chromatography–Q Exactive Orbitrap tandem mass spectrometry were integrated for the component analysis of 18 batches of Citri Reticulatae Pericarpium from 12 cultivars for the first time. A total of 57 components from the supercritical CO2 fluid extracts were demonstrably or tentatively identified by the obtained parent peaks, fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The color of CRP is mainly composed of naringin (a kind of flavonoids) and carotenoids. 6 , 7 Generally, the pericarp contains natural pigment which can stain the surface of human skin, but the pigment can be disappeared after cleaning or scratching. In this case, the patient suffered blackish pigmentation on the toenails after using CRP solution which could not be removed after cleaning or scratching with alcohol cotton ball or razor blade.…”
Section: Discussionmentioning
confidence: 99%
“…The color of CRP is mainly composed of naringin (a kind of flavonoids) and carotenoids. 6 , 7 Generally, the pericarp contains natural pigment which can stain the surface of human skin, but the pigment can be disappeared after cleaning or scratching. In this case, the patient suffered blackish pigmentation on the toenails after using CRP solution which could not be removed after cleaning or scratching with alcohol cotton ball or razor blade.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Fu et al (2017) suggested that the content of TFs in CRCP decreased during storage. The chemical content of CRCP was correlated with the originated place, drying method, storage environment, microbial quantity, and other factors (He et al, 2019;Li et al, 2020;Zheng, Liu et al, 2020). Therefore, the differences among samples may lead to inconsistencies in reported results.…”
Section: Dynamic Variation Of Tfs Tpmfs and Tpas In Crcp During Storagementioning
confidence: 99%
“…However, most of the medicinal herbs used in the reported literature were purchased from markets. It is difficult to keep the unified quality of commercial CRCP due to several factors, such as the tree age, original place, harvested period, drying process, and storage environment (Luo et al, 2018;Zheng et al, 2021;Zheng, Liu et al, 2020). In addition, previous studies primarily focused on fully matured CRCP, whereas only few studies applied CRCP harvested at other stages for storage research.…”
Section: Introductionmentioning
confidence: 99%
“…BCT is enriched with flavonoids, polyphenols and organic acids, and its pharmacological action is mainly anti-oxidation [9]. The flavonoids, alkaloids and coumarins are the common constituents in AFI [10,[11][12][13] and CRP [10,14], in which the flavonoids exhibit the anti-atherosclerosis effect [15]. Furthermore, the pungent phytochemicals and diarylheptanoids are the principal components in ZRR [16,17] with antioxidant, anti-inflammatory, and antiemetic effects [18].…”
Section: Introductionmentioning
confidence: 99%